2021
DOI: 10.3390/agronomy11112287
|View full text |Cite
|
Sign up to set email alerts
|

Desert Locust Stopped by Tibetan Highlands during the 2020 Upsurge

Abstract: Desert locust is an important pest to agriculture. In 2019–2020, a major upsurge originated in the southern Arabian Peninsula and gradually spread to east Africa, then to south-west Asia, as far as Pakistan and India, even reaching Nepal, resulting in major agricultural losses. For the first time, a few swarms entered southern Tibet. Using field observations and experiments, we studied their path to the Tibetan plateau and their behavior at these very high altitudes. The locusts moved up the Tibetan valleys fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Climate, soil conditions, and land use that may influence the distribution and outbreaks of desert locusts have been considered in many studies [14,15,27], but few researchers have considered all factors when determining the current and future threats posed by desert locusts on a global scale. The currently known occurrences of desert locusts also showed that topographic factors may also be important factors affecting the migration of desert locusts, and mountains may be a major obstacle in preventing desert locust invasion [12]. In this study, we found that climate factors most strongly impact the distribution of desert locusts, and the climate factor with the strongest impact is the minimum temperature of the coldest month.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Climate, soil conditions, and land use that may influence the distribution and outbreaks of desert locusts have been considered in many studies [14,15,27], but few researchers have considered all factors when determining the current and future threats posed by desert locusts on a global scale. The currently known occurrences of desert locusts also showed that topographic factors may also be important factors affecting the migration of desert locusts, and mountains may be a major obstacle in preventing desert locust invasion [12]. In this study, we found that climate factors most strongly impact the distribution of desert locusts, and the climate factor with the strongest impact is the minimum temperature of the coldest month.…”
Section: Discussionsupporting
confidence: 52%
“…These three land use factors are all characterized by the lack of forest cover, and forest cover is usually associated with humidity and low temperature, which are not conducive to the reproduction and survival of desert locusts, and so are key factors limiting the distribution of desert locusts. Although the known occurrences of desert locusts showed that high-altitude mountains are key barriers limiting the distribution of desert locusts [12], and the elevation importance value was only 0.022 (Table 1). The factors that had a stronger impact on its global distribution were climate factors, rather than relatively isolated high-altitude mountains and their elevation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [72], for the first time, studied the behavior of Desert Locust swarms in southern Tibet at very high altitudes of up to 5400 m. They show that low temperatures, high humidity and low atmospheric oxygen put the locusts under severe stress and that the Himalayan mountains provided an important natural barrier that limited the northward expansion of Desert Locust populations.…”
Section: Summary Of Articles Included In This Special Issuementioning
confidence: 99%